KATA KERJA BANTU MODAL DALAM NASKAH FILM TED KARYA SETH MACFARLANE, ALEC SULKIN DAN WELLESLEY WILD - SHALEH, ARDI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This study is attempt to describe, clasify and analyze modal verb in The film script Ted by Seth Macfarlane , Alec Sulkin and Wellesley Wild. The auxiliary verb modals are auxiliary words that serve as